1975
DOI: 10.1207/s15327906mbr1001_5
|View full text |Cite
|
Sign up to set email alerts
|

A Multivariate Analysis of Selected Class Characteristic and Student Rating of Instruction

Abstract: This study examined the relationship between selected class characteristics and student ratings of instructors. A large number of classes (N = 1247)and students (over 33,000) a t a large Midwestern University provided the data for this study. The results indicated that the class characteristics that had the strongest influence on the results of instructor ratings were the grades expected by students and the percentage of students in the class taking the course as an elective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 4 publications
1
35
0
Order By: Relevance
“…Lecturers differed from course to course, the content of courses varied and the students differed. The results of the Likert scale ratings used in this study were predicted on the basis of previous research findings (Pohlmann, 1975). The three aspects of the course including 'human related factors', 'feelings about course content' and 'hygiene factors' were all regarded more favourably by students on the elective course than by those on the required course.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Lecturers differed from course to course, the content of courses varied and the students differed. The results of the Likert scale ratings used in this study were predicted on the basis of previous research findings (Pohlmann, 1975). The three aspects of the course including 'human related factors', 'feelings about course content' and 'hygiene factors' were all regarded more favourably by students on the elective course than by those on the required course.…”
Section: Discussionmentioning
confidence: 75%
“…In a subsequent study by Gage (1961) this was also found to be the case, although the study only used a series of Likert style rating scales. In another study, Pohlmann (1975), evaluated five aspects of courses, namely an overall view of how good the course was, how interested the tutor was in each student, how difficult the student found the course, whether assignments were clearly marked and how good the tutors actual presentation was. Pohlmann found that, employing these factors undergraduate students' evaluations on the elective courses were better on all measures than for the required courses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Aleamoni and Graham (1974) Goodhartz (1948), Guthrie (1954), Hildebrand et al (1971), Hillery and Yuk (1974), Jiobu and Pollis (1971), and Solomon (1966) found no relationship between class size and student ratings. Some investigators have also reported curvilinear relationships between class size and student ratings (Gage, 1961;Kohlan, 1973;Lovell and Haner, 1955;Marsh et al, 1979;Pohlmann, 1975;Wood et al, 1974).…”
Section: Class Sizementioning
confidence: 99%
“…As such, the teaching of these courses has been debated among faculty over the years as being 'more difficult' to teach. To that end, several large studies consistently find teachers of elective courses receive more favorable evaluations than their colleagues teaching required classes (Drago & Wagner, 2004;Whitten & Umble;Pohlmann, 1975;Lovell & Haner, 1955). Researchers have suggested a number of possible reasons for these findings, including student attitudes towards the topic, the quantitative nature of some of the required courses, student perception of quality, the professor's teaching style (Bosshardt, 2001;Marsh & Roche, 1997) and the students interest and engagement (Darby, 2006a); all of which affect STEs.…”
Section: Class Type (Core or Elective)mentioning
confidence: 99%